CONTINENTAL RIFT ARCHITECTURE AND PATTERNS OF MAGMA MIGRATION: A DYNAMIC ANALYSIS BASED ON CENTRIFUGE MODELS - Corti G.; Innocenti F.; Bonini M.; Sokoutis D.; Cloetingh S.; Manetti P.; Mulugeta G. (My University, 2004)
Small-scale centrifuge models were used to investigate the role of continental rift structure in controlling patterns of magma migration and emplacement. Experiments considered the reactivation of weakness zones in the lower crust and the presence of magma at Moho depths. Results suggest that surface deformation, which reflects the weakness zone geometry, exerts a major control on patterns of magma migration. In the case of a single rift segment, the experimental lower crust and magma were both transferred in an extension-parallel direction toward the rift flanks. This lateral migration reflected the dominance of far-field stresses over extension-induced buoyancy forces. Local pressure gradients favored the raise of experimental magma in correspondence of marginal grabens. The lateral migration gave rise to major accumulations below the footwall of major boundary faults, providing the magma source able to feed off-axis volcanoes in nature, as inferred for the Main Ethiopian Rift. In the case of two offset rift segments, a major transfer zone developed. This transfer zone was characterized by prominent experimental lower crust doming and strong magma accumulation. Dynamic analysis showed that the transfer zone development caused a strong pressure difference in a rift-parallel direction, which dominated over the far-field thinning. Owing to this pressure gradient, almost all the underplated experimental magma collected below the lower crust dome, suggesting a rift-parallel (extension-orthogonal) migration. This process has a direct relevance for the localization of magmatic activity at transfer zones in natural continental rifts, such as in the Western Branch of the East African Rift System. (2004), Continental rift architecture and patterns of magma migration: A dynamic analysis based on centrifuge models, Tectonics, 23, TC2012, doi:10.1029/ 2003TC001561.
Keywords: continental rifting; magma migration; analogue modeling